ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF THE BLOOD OF GAMMA RADIATION TREATED GRADE - León, K. (2007)
Blood is irradiated degree (Croton lechleri​​) powder to different doses of gamma (5, 8, 15, 25 and 40kGy) radiation. The antioxidant properties of the samples decreases with increasing irradiation dose. However, no noticeable changes were observed in their UV-visible and infrared spectra, which suggests to us that there were no major changes in the constitution of latex powder after irradiation. Also, the antimicrobial properties of aqueous-alcoholic solutions of these irradiated samples, embedded in chitosan-PVA films, against bacterial strains Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were not changed compared with blood samples unirradiated grade. These films have only Irente activity to S. aureus.